2001
DOI: 10.1007/pl00001151
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Location Calibration of the European Arctic

Abstract: Ð A crustal velocity model has been developed for Fennoscandia, the Baltic shield and adjacent areas. This model represents a simpli®ed average of various models developed for parts of this region. We show that P-wave travel times calculated with this model provide an excellent ®t to observations at the Fennoscandian, KRSC and IRIS station networks for a set of seismic events with known or very well-constrained locations. The station-event paths cover large parts of Western Russia and the Barents Sea, thus ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(16 citation statements)
references
References 5 publications
0
13
0
3
Order By: Relevance
“…Fig. 12), a slightly modified version of the Barents Sea model by Kremenetskaya et al (2001) on top of model ak135 (Kennett et al 1995), is superior to other models for locating seismic events in the wider Barents Sea region. However, because of the known differences in the crustal structure, any 1-D model will have its limits in describing the velocity structure of the region.…”
Section: Barentsmentioning
confidence: 98%
See 1 more Smart Citation
“…Fig. 12), a slightly modified version of the Barents Sea model by Kremenetskaya et al (2001) on top of model ak135 (Kennett et al 1995), is superior to other models for locating seismic events in the wider Barents Sea region. However, because of the known differences in the crustal structure, any 1-D model will have its limits in describing the velocity structure of the region.…”
Section: Barentsmentioning
confidence: 98%
“…monitoring seismic activity within the region, which includes the Soviet nuclear test site at Novaya Zemlya. Kremenetskaya et al (2001) published a 1-D velocity model for the wider Barents Sea region. Hicks et al (2004) demonstrated that the 1-D model called Barey (Schweitzer & Kennett 2002, cf.…”
Section: Barentsmentioning
confidence: 99%
“…The new 3-D velocity model developed here may also replace the simple crustal velocity models of Kremenetskaya et al (2001) and Schweitzer & Kennett (2002) derived from regional seismological analysis in the European Arctic. These models are mainly averages of various local models and, therefore, do not account for the geological diversity found in the Barents Sea region.…”
Section: Previous Crustal Modelsmentioning
confidence: 99%
“…В качестве скоростных моделей были опробованы следующие 1D модели: BARENTS [Kremenetskaya et al, 2001], BAREY и BAREZ [Schweitzer, Kennett, 2007] и NORP [Морозов, Ваганова, 2011]. Модель BARENTS была разработана для Фенноскандии, Балтийского щита и прилегающих районов.…”
Section: Nunclassified